The Association between Occlusion and Attrition - Ritchard Anthony; Welsh Alan H.; Donnelly Christine (Australasian Orthodontic Journal, 1992)
The purpose of this study was to identify variables of malocclusion that might be associated with attrition and then to quantify the relationship between these variables and attrition. The results of this study indicate that, with all other factors held constant, a patient's attrition score tends to: increase with age, increase with bite depth, decrease initially with overjet until a critical value and then increase, and be unaffected by sex, interincisal angle, U1 to NA angle, Angle classification, posterior or anterior cross bites. Further, we discuss the statistical treatment of data of this kind and emphasize the importance of a professional approach to analysis.